Clinical significance of prognostic nutritional index (PNI)-monocyte-to-lymphocyte ratio (MLR)-platelet (PLT) score on postoperative outcomes in non-metastatic clear cell renal cell carcinoma - Wenming Ren; Hao Zhang; Li Cheng; Yu Zhang; Chenglin Yang; Liang Nie; Congcong Yang; Peng Yao; Jie Han; Dong Zhuo (BMC Surgery, 2023)
Abstract Background Prognositic nutritional index (PNI), monocyte-to-lymphocyte ratio (MLR) and platelet (PLT) are associated with tumor survival in many human malignancies. Whereas, no study combined PNI-MLR-PLT score and indicated its predictive significance on the prognosis of patients with non-metastatic clear cell renal cell carcinoma (ccRCC). Methods In this study, we retrospectively collected the clinicopathological characteristics and prognostic data from 164 cases of non-metastatic ccRCC and aimed to determine the clinical significance of PNI-MLR-PLT score on patients’ outcomes after surgery. The optimal cut-off values of PNI (PNI > 47.40 vs PNI < 47.40), MLR (MLR > 0.31 vs MLR < 0.31) and PLT (PLT > 245 vs PLT < 245) were identified with relative operating characteristic (ROC) curve analysis. The PNI-MLR-PLT score system was established by the value of three indexes, each indication was assigned a score of 0 or 1. Overall survival (OS) and metastasis-free survival (MFS) were analyzed using Kaplan–Meier estimate and Cox regression models. Results The mean follow-up period was 85.67 months. Eight (5.0%) patients died, 4 (2.0%) relapsed, and 7 (4.0%) developed metastasis after surgery. The 3-year OS and MFS rates were 98.2% and 97.6%, and the 5-year OS and MFS rates were both 90.2%. Our results suggested that PNI-MLR-PLT score negatively correlated with pathological T stage and tumor grade. Survival outcomes revealed that lower PNI-MLR-PLT score is associated with inferior OS (P < 0.001) and MFS (P < 0.001) after surgery. Subgroup analysis regarding pathological T stage, tumor grade and surgical modalities obtained consistent results. univariable and multivariable Cox analysis showed that high PNI-MLR-PLT score was the independent protective factor of tumor survival in non-metastatic ccRCC patients. Conclusions Our data suggested that PNI-MLR-PLT score could serve as a promising independent prognostic factor in patients with non-metastatic ccRCC.